Digital signal processing in MIMO radars with time-multiplexed transmit signals - Đaković, Borko B.; Simić, Slobodan M.; Trivundža, Lidija M.; Ristić, Aleksandar G. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: A current topic of significant research and development efforts in the field of radar systems is MIMO (Multiple-Input-Multiple-Output) radar technology. MIMO radars represent a revolutionary step forward in radar technology, as the use of multiple transmitting antennas that emit orthogonal waveforms enables improved detection and angular resolution. To achieve effective results, high-quality digital signal processing and the application of advanced algorithms are essential for obtaining target information. This paper places special emphasis on coherent MIMO radars, with the objective of enhancing angular resolution. Time-multiplexing of transmit signals is applied as a primary method to achieve orthogonality between signals, utilizing a Frequency Modulated Continuous Wave (FMCW) signal as the foundation for the transmit waveform. The aim of this paper is to provide and explain the fundamentals of digital signal processing in MIMO radars, present analytical expressions, and validate them through simulation and experimental verification.Methods: The theoretical foundations are presented, with the Discrete Fourier Transform (DFT) used as a primary tool in digital signal processing to obtain information about the distance, velocity, and azimuth of the target. A simulation was developed in the MATLAB software package to analyze the performance of the radar system model. Experimental verification was conducted, where specific scenarios were recorded using the radar platform PUP_DUAL24P_T2R4, and the collected data was subsequently processed. The MATLAB functions MIMOFMCW and procDC were written to generate simulation samples of echo signals and to automate signal processing and the display of characteristic Range-Velocity and Range-Angle matrices.Results: The simulation and experimental verification confirm the validity of the theoretical foundations related to digital signal processing in MIMO radars, and the target parameters can be clearly determined.Conclusion: The Discrete Fourier Transform is a simple tool that provides satisfactory results for determining the range, velocity, and angle of targets. FMCW radars offer accuracy in determining range and velocity, while the MIMO mode enhances angular resolution. The DFT algorithm is capable of determining the target angle, but with a certain error, making the use of high-resolution methods necessary for more accurate angle determination.
Keywords: MIMO; radar; TDM; FMCW; radar data cube; DFT; beat frequency; virtual antenna